Potential beta-glucosidase inhibitor from Malaysian medical plants - Ahmad Barkat, Anumsima; Jamal, Parveen; Amid, Azura (2009)
Diabetes is one of the chronic diseases affecting worldwide population. Presently, there is a growing interest in herbal remedies due to the side effects associated with the use of insulin and oral hypoglycaemic agents for diabetic patient. Therefore an investigation is required in a bionetwork rich and industrially-developed country like Malaysia to use alternative approaches to treat diabetics, such as plant based medicine. In this study, forty types of Malaysian antidiabetic plants were examined on the basis of their uses in traditional medicines throughout Southeast Asia, to develop an understanding of the distribution and to give an assessment of the diversity present in the selected plants. Extracts of all 40 species of Malaysian medicinal plants were examined for -glucosidase inhibition using an in-vitro model. Most of the plants showed varying degree of inhibitory activity (%) but Centella asiatica had the maximum percentage of -glucosidase inhibitory activity (99.03%) while the second best is Morinda citrifolia with 96.37% inhibitory activity. Another two potential plants which gave higher inhibitory activity were Cucumis sativus (93.95%) and Euphorbia tircalli L. (90.56%). These potential plants with -glucosidase inhibitory activity can be a hope for millions for treatment of diabetes and will also help in reducing the dependence on synthetic drugs in the future.